1986
DOI: 10.1180/claymin.1986.021.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Facies-related diagenesis in the Main Claymore Oilfield sandstones

Abstract: Four major sedimentary sequences of the Triassic and Upper Jurassic of the Main Claymore Oilfield of the North Sea each contain a characteristic suite of diagenetic minerals and fabrics. (1) Triassic Skagerrak Formation fluvial sandstones contain early authigenic pore-lining smectite, together with kaolinite and chlorite which form grain replacements and pore fills. Quartz and feldspar overgrowths are minor. Ferroan dolomite forms a late diagenetic patchy poikilotopic cement. Smectite is converted to illite-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…whereas marine sandstones of, for example, the Claymore Field (Spark & Trewin, 1986) or the Fulmar Field (Stewart, 1986) show comparatively little secondary porosity. This gives strong support to Bjorlykke (1980Bjorlykke ( , 1983Bjorlykke ( , 1984, who regards much of the secondary porosity in North Sea sandstones to have resulted from the introduction of meteoric waters early in diagenesis.…”
Section: Gromentioning
confidence: 99%
“…whereas marine sandstones of, for example, the Claymore Field (Spark & Trewin, 1986) or the Fulmar Field (Stewart, 1986) show comparatively little secondary porosity. This gives strong support to Bjorlykke (1980Bjorlykke ( , 1983Bjorlykke ( , 1984, who regards much of the secondary porosity in North Sea sandstones to have resulted from the introduction of meteoric waters early in diagenesis.…”
Section: Gromentioning
confidence: 99%
“…In addition, the effect of chlorite coating in sandstones from different places is well known [3][4][5][6][7][8][9][10]. Micro-quartz [12,13], illite [2,11] and kaolinite [14] were also documented.…”
Section: Occurrence and Existing Statementioning
confidence: 99%
“…There have been many studies on the effect of chlorite coats on reservoir quality [3][4][5][6][7][8][9][10]. In addition to chlorite coating, clay grain coats include illite coating [2,11], quartz overgrowth coating [12,13] and kaolinite coating [14]. Additionally, organic acids are also important to the dissolution of reservoirs, which result from the maturation of organic matter in shales or mudstone adjacent to sandstone [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ramm and Forsberg (1991) reported in a study of Upper Jurassic sandstones of the Gyda area that sandstones containing microcrystalline quartz overgrowths had higher porosities (around 20-22% at 4.1-4.2 km) than sandstones that contained macroquartz overgrowth. In addition, Spark and Trewin (1986) reported porosity preservation in the Ten Foot Sandstone of the Claymore field, North Sea, which they attributed to early formation of discrete quartz crystals. Spark and Trewin (1986) also suggested that the sandstones were supersaturated with respect to silica because discrete crystals rather than syntaxial quartz overgrowths developed.…”
Section: Porosity and Permeabilitymentioning
confidence: 99%
“…In addition, Spark and Trewin (1986) reported porosity preservation in the Ten Foot Sandstone of the Claymore field, North Sea, which they attributed to early formation of discrete quartz crystals. Spark and Trewin (1986) also suggested that the sandstones were supersaturated with respect to silica because discrete crystals rather than syntaxial quartz overgrowths developed. They considered the source of silica to be a result of dewatering of adjacent shales.…”
Section: Porosity and Permeabilitymentioning
confidence: 99%